The use oflangmuir-blodgett films of hematin mixed with arachidic acid to detect carbon monoxide gas - Muhamad Mat Salleh; A. S. Belal; Muhamad Yahaya (Universiti Kebangsaan Malaysia, 1997)
There is great interest in gas sensing especially for toxic gases such as carbon monoxide. This paper reports the use of Langmuir-Blodgett films of hematin mixed with arachidic acid to detect carbon monoxide gas in nitrogen at room temperature. The detection was studied based on changes in the optical absorption and reflection of the film using a spectrophotometer and an optical fiber system, respectively. The absorption spectra of a 20 layers LB film decreased when exposed to 10, 100, 1000 ppm CO gas, and had fast recovery time when the gas flow was stopped. An optical fiber system consists of a laser diode as light source, a fiber reflectance probe, thin film sample on a reflecting mirror and a light detector was setup. Using this system it was found that the intensity of the reflected light increased when the film was exposed to the gas. The sensing sensitivity of the films increased after the films were annealed for one hour at 100°C. The result is explained using the atomic force microscope (AFM) images of the LB films taken before and after annealing.